Escuta e interpretação na clínica de linguagem - Pollonio, Cláudia Fernanda (2011)
This study was conducted in accordance with the reflections on symptomatic speech and language therapy developed within the LAEL-CNPq Research Group: Language acquisition, pathology and clinic, coordinated by Maria Francisca Lier-DeVitto and Lúcia Arantes. The discussion carried on was motivated by the challenging questions related to the notions of listening and interpretation, which are advanced in the realm of the above mentioned research group. Two distinct domains underlie the theoretical proposals concerning those themes: Linguistics, more particularly, the European Structuralism (Saussure, Jakobson) and Psychoalysis (Freud and Lacan). No doubt, the Interactionism in Language Acquisition is an assumed theoretical basis. The structural articulation which links child-language-other, proposed by De Lemos (1992), allowed for the conclusion that there is strong connection between listening and interpretation. In the present discussion, Freud is taken as a landmark on the subject matter approached here, since the two clinical notions discussed in the present study were introduced by him. That is why part of it is concentrated on the exploitation Freud made about them (as well as on those advanced by Lacan, after him). The assumptions sketched out below should provide a specific clinical contour to the notions of listening and interpretation to the Language Clinic: (1) transliteration, that is, privilege is given to the manifest significant chain; (2) singularity, that is, it is sustained that each speech manifestations is unique. The fundamental hypothesis advanced in this study is that changes in speech are determined by linguistic causality, i.e., they come up as an effect of the interplay between the patient s speech and the therapist s interpretation. Therefore, this thesis puts forward an alternative proposal that emphasizes the importance of theoretical commitment as primary condition for the construction of the specific notions of listening and interpretation. It must be added that segments taken from some clinical cases were presented in order to clarify the discussion carried on